Customer Price Sensitivity as a Basis for Moderation in Satisfaction among Mobile Customers - G., Rejikumar (Indian Journal of Marketing, 2013)
The present study was designed to examine the impact of customer price sensitivity on customer satisfaction in the mobile telecom sector. The major antecedent that develops customer satisfaction was considered as Perceived Service Quality and, therefore, an attempt was made to develop and validate a scale for measuring Perceived Service Quality in the mobile telecom context. Variance-based structural equation modeling was used to analyze the relationships among different constructs considered in the study. The various constructs used in the study were conceptualized as reflective or formative based on theoretical considerations. The study found that the dimensions such as Network Quality, Human Interaction Quality, Product Mix, Infrastructure related aspects, and Image influenced service quality perceptions of the customers in the mobile telecom context. The Price Sensitiveness of the customers explained the possible fluctuations in business volumes due to price changes. This study could identify the impact of Price Sensitivity as a psychographic variable that moderated customers’ satisfaction significantly in the mobile telecom context. The mobile telecom sector, being a market for frequent innovations in service offers and pricing schemes, should seriously look into customer price sensitivity to control customer defections.